Legal-linguistic analysis of insults in the Uzbek language - Maqsudaliyeva, Yodgorkhon Nu’monjon qizi (The Lingua Spectrum, 2026)
This scientific article provides a comprehensive analysis of coarse and non-literary vocabulary found in the Uzbek language, their origins, social and regional characteristics. The study examines local, dialect-specific and borrowed slang units based on examples. In particular, the lexical-semantic features of abusive words, their shades and five spheres of usage were analyzed at a new level. Furthermore, the interpretations of vulgarisms presented in the “Explanatory Dictionary of the Uzbek Language” were fully revealed. During the research, using comparative-analytical and expert methods, words that defame honor or are abusive were studied from a legal perspective. The article investigates coarse vocabulary from the viewpoints of linguistics, psycholinguistics and sociolinguistics. The semantic field of language units, connotative meanings and pragmatic functions are thoroughly illuminated. Additionally, the socio-psychological impact of non-literary words, the reasons and contexts of their usage in speech are examined as an independent object of analysis. The authors also examined the etymology of lexical units, dialectal variants and modern changes. The research results are of practical importance for the development of linguistic science and improvement of lexicographic explanatory dictionaries. This study allows for a deeper understanding of the rich lexical heritage of the Uzbek language.